The problem of ensuring the sovereignty of EU members states in modern legal and public discourse - Ye. Novikov (Юридичний часопис Національної академії внутрішніх справ)
This study presents a theoretical analysis of the concept of sovereignty and explores some of the peculiarities of its implementation in the policies of European states in the context of regional integration, which is relevant in view of the UKʼs withdrawal from the European Union and critical assessments of EU policies by Eastern European countries. The purpose of this study was to examine changes in the concept of state sovereignty under the influence of integration processes. The research methodology was based on a critical analysis and systematic review of publications by leading researchers in the field of European politics, law and sovereignty theory, as well as concepts of European sovereignty. This helped to consider different perspectives on the change of sovereignty in the context of the development of supranational and intergovernmental institutions of the EU. In particular, how the concept of “European sovereignty” is used in the legitimation strategies of political actors supporting integration and supranational governance. The results of the study indicate changes in the definition of sovereignty in contemporary European politics. On the other hand, EU member states are facing less control over many national functions through supranational institutions such as the European Commission and the Court of Justice of the European Union, which will lead to partial restrictions on control over certain areas of domestic and foreign policy. Thus, this study has proved that supranational governance is developing as a process that not only expands the EUʼs sphere of power, but also transforms the traditional concept of sovereignty, making it more dynamic and more adapted to modern political realities. The conclusions drawn can serve to form a new model of integration policy that reflects political and social needs within the framework of European integration and is able to ensure a balanced interaction between nation states and supranational structures